Feedback as "shadow of the present" : an alternative to reputation systems for e-marketplaces - Li, Qin (2013)
A reputation system is a common approach to induce sellers' good conduct in an e-marketplace, where feedback about a seller will be used by a potential future buyer to decide whether to conduct a transaction with the seller. However, reputation systems suffer from some inherent problems. We propose a novel approach that changes the fundamental role of feedback - the impact of feedback is exerted only to the transaction that the feedback is obtained from, but not future transactions. Consequently, some inherent problems of reputation systems no longer apply in our scheme. Our approach thus offers an alternative to traditional reputation systems, to induce sellers' good conduct.